The Ẓāhirī School between East and West: Tracing the Development of Islamic Legal Literalism from Baghdad to Cordoba - Omar García Sánchez; Karim Rodríguez Pérez; Yasmina Fernández Ruiz; José Miguel Puerta Vílchez; Mohammed Ibrahim El Idrissi (Indonesian Journal of Islamic Law, 2025)
This article explores the historical development and intellectual trajectory of the Ẓāhirī school of Islamic jurisprudence, focusing on its transition from Baghdad in the East to Cordoba in the West. The study investigates how the school’s distinctive approach to legal literalism (ẓāhir) evolved within varying cultural, political, and intellectual contexts. Using a comparative textual analysis of foundational Ẓāhirī works, including those by Dāwūd al-Ẓāhirī and Ibn Ḥazm, the research examines the principles underpinning the school’s strict adherence to apparent meanings in legal interpretation. The findings reveal that while the Ẓāhirī school maintained its core commitment to textual literalism, its methodologies and applications adapted to regional dynamics. In Baghdad, the Ẓāhirī approach emerged as a critique of rationalist and analogical reasoning, asserting the primacy of Qur'anic and Prophetic texts. Under Ibn Ḥazm’s leadership in Cordoba, the school flourished in response to Andalusian intellectual currents and debates with other schools of thought. These developments underscore the Ẓāhirī school's dual identity as both a challenger of prevailing jurisprudential trends and a product of its socio-political milieu. This study concludes that the evolution of the Ẓāhirī school highlights the dynamic interplay between textual fidelity and contextual adaptation in Islamic legal history. By tracing its development across two distinct regions, the research contributes to broader discussions on the diversification of Islamic jurisprudence and the role of literalism in shaping legal discourses across time and space.